Reestruturação do sistema bancário argentino e brasileiro na década de 90 - Belusso, Sabrina Lilian (2006)
This dissertation analyses the changes in the Brazilian and Argentinean bank system in the 90 s decade under a context of many transformations. It makes an approach of the legal aspects, the occurrence and effects of crisis, reformations and foreigner banks opening. The dissertation is divided into five chapters. In the first chapter we make a characterization and the evolution of the Financial System, followed by chapter two where we analyze the role of the banks in an integration process. Chapter III deals about the main changes in the Argentinean and Brazilian laws relative to the financial and bank systems. In chapter IV deals with the regulation and with the crisis that reached the Brazilian and Argentinean bank system in the 90 s. And finally, chapter V is about the opening of foreigner banks and its relation with the matter of concentration in the Brazilian and Argentinean bank system in the 90 s decade. The reorganization in the Brazilian and Argentinean Bank System derived from alterations in the context where the bank institutions are established resulted, as its main characteristic, in a bank system widely open to foreigner capital and consequently, more concentrated and internationalized. The increasing liberalization verified provides a higher interdependence and integration among financial systems standing out the importance of a harmonization and adaptation in the sector.